Undang-Undang Desa Sebagai Legitimasi Desa (Desa Dalam Hukum Ketatanegaraan Indonesia) - Aji, Ian (Legal Standing : Jurnal Ilmu Hukum, 2017)
Position the village in a country is very important, because the village is the spearhead of a government. The existence of the village only as a supplement to administrative, so the existence of a very backward village either of its human resources and in terms of management of natural resources are owned and infrastructure development tends to be slow. It makes villagers to make an exodus to urban areas for improvement of life. Recognition of the structure provided in the central government through a law on village administration look encouraging, but the relation to the welfare of the government does not pay attention. No wonder if the government runs a program is often different. The workload is heavy village government is not matched by right. The village as a vanguard of government, the village government should be able to overcome all the problems that arise in the community, with peace and peaceful village can increase unity and national unity of Indonesia